Emotional intelligence and anxiety disorder probabilities in grappling and striking combat sport athletes: comparison with regression analysis - Fernandez, M. M.; Perez, D. I. V.; Aedo-Munoz, E.; Barreto, L. B. M.; Brito, C. J.; Miarka, B.; Diaz-de-Durana, A. L. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2023)
Background. Combat sports are separated into striking and grappling types. Both have an essential impact on the Summer Olympics medal results. Psychological analysis is a way to understand the factors explaining success in elite-level combat athletes; however, very little research has focused on emotional intelligence, verifying the prevalence of anxiety disorders. Problem and Aim. This study aimed to compare emotional intelligence and cognitive, motor, physiological and total anxiety between striking and grappling athletes. Methods. Our sample was composed of 382 athletes, 299 from grappling and 89 from striking combat. All samples were analyzed by emotional intelligence using the Trait-Meta Mood Scale and by anxiety, using Inventory of situations and anxiety responses, p=0.05. Results. The main results indicated that grappling athletes showed a higher score for anxiety before the evaluation [54 (27; 79) vs. 49 (26; 73); p=0.04], before habitual and daily situations [7 (3; 18) vs. 6 (3; 14); p=0.04], emotional perception [23 (18; 28) vs. 22 (18; 27); (p=0.03)] and a lower score for emotional regulation [29 (24; 33) vs. 30 (25; 33); p=0.01]. The regression performed showed a significant effect (p=0.014) for anxiety and emotional intelligence comparing grappling versus striking, with higher ODD for the Inventory of situations and anxiety responses (Exp B - 1.029). Conclusions. Our results showed that grapplers presented higher interpersonal, cognitive and motor anxieties, and lower levels of emotional comprehension than striking athletes. Furthermore, the regression model demonstrated ~30% probability of increasing interpersonal anxiety in grappling athletes rather than strikers.